Magnons on the Shastry-Sutherland lattice - Chua, Xin Rong (2016)
The crux of this project is to study the magnetization processes of the geometrically frustrated Shastry-Sutherland lattice when subjected to various interactions. Experimental results showed the formation of plateaus at rational values of full magnetization. In order to understand the underlying principle behind these magnetization plateaus, theoretical physicists have been dedicating their effort in this field of research. The project aims to reproduce results in literatures through analytical means. In particular, the project will derive the 1/3 plateau in the Ising limit as well as both 1/3 and 1/2 plateaus in the Heisenberg model. After an attempt to understand the physics behind these plateaus, we move on to include a weak anisotropic Dzyaloshinskii–Moriya perturbation in the two models. Investigation of the magnetization graphs are done through analytical means and a computational method known as Exact Diagonalization.